Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae) - Kosterin, Oleg E.; Kompier, Tom (Zootaxa, 2018)
Amphicnemis valentini sp. nov. is described from the Ream Peninsula of Cambodia (holotype: Cambodia, Preah Sihanouk Province, Ream Peninsula, 10.52258 N 103.69556 E, RMNH) and Phú Quốc Island, Kien Giang Province of Vietnam, both in the Cardamom ecoregion. It is similar to A. gracilis Krüger, 1898, which occurs in Peninsular Malaysia and Sumatra, but differs from it by a long process on the male prothorax.